New synthetic routes to protected purine 2'-O-methylriboside-3'-O-phosphoramidites using a novel alkylation procedure. - Sproat, B S (1990)
A highly selective alkylation procedure has been developed enabling new synthetic routes to be established for protected purine 2'-O-methylriboside-3'-O-phosphoramidites; building blocks for the assembly of 2'-O-methyloligoribonucleotides. The new procedure avoids the use of the highly toxic and potentially explosive reagent diazomethane and is far superior to the use of silver oxide/methyl iodide. Moreover, the use of highly versatile key intermediates will enable the synthesis of a wide variety of base modified analogues as well as other 2'-O-alkylriboside derivatives.